DOES CULTURAL DIVERSITY MATTER FOR TEAM PERFORMANCE IN MULTINATIONAL COMPANIES? AN ANALYSIS OF CONFLICT, COMMUNICATION, SOCIAL INTEGRATION, CREATIVITY AND SATISFACTION - OBSUWAN, SORNSAWAN; CHANDRASHEKAR, DEEPAK; KRAUS, SASCHA; BREM, ALEXANDER; BOUNCKEN, RICARDA (International journal of innovation management, 2021)
Team performance is key in each organisation. Hence, cultural effects in teams are a relevant matter of subject clarifying the ambiguous findings from previous research. With this background, we investigate how the macro-constructs of conflict, communication effectiveness, social integration, creativity and satisfaction interact with cultural diversity on team performance in an environment characterised by a largely homogeneous and ethnic workforce. We test our hypotheses on a sample of firms in Thailand. Our results indicate that creativity and satisfaction have a significant positive impact on team performance whereas cultural diversity has a significant positive impact on influencing conflict in a team-based environment. However, cultural diversity has no significant impact on communication effectiveness and social integration, and it has no significant impact on team performance. The key theoretical contributions from our study are that cultural diversity can contribute to conflict even in a team composition that is seemingly cohesive and homogeneous in nature. Further, our study establishes that creativity and satisfaction have a positive effect on team performance even in the context of a homogeneous and ethnically majority-based team. For the practitioners, the results of the study indicate that initial actions need to be taken by the leaders of multicultural teams as they create teams to avoid the initial pitfalls due to conflict.